Impact of governance on poverty, public expenditure and trade in sub Saharan African countries - Madina, Dankumo Ali (2021)
Globally, nations and international organizations such as IMF, World Bank and Transparency International, try to promote good governance, due to its significance to growth and development, while frowning at bad ones. Unfortunately, in the SSA region, governance in almost all the countries in the region is poor with the lowest measures of governance when matched with other regions of the World as confirmed by its separate governance measures of control of corruption (-0.582) and political stability (-0.526). Other manifestations of poor governance are the poor implementation of policies and programmes, no transparency and accountability, non-functional legal framework, and there are also coups, crisis, and civil wars etc., which affects growth and poverty through its determinants- public expenditure and trade. Firstly, the study investigated the impact of governance on poverty via interaction with public expenditure in the region applying system GMM techniques for unbalanced panel data for 46 countries of SSA spanning over the 1996 – 2019 period. The study discovers that the interaction of governance (corruption and political instability) and public expenditure increases poverty. The marginal effects also show that governance – corruption and political instability – at both minimum and medium levels increases poverty in SSA, but is insignificant at the maximum levels. This suggests that corruption and political instability has a significant role in mediating the effect of public expenditure on poverty in the SSA. It then follows that if SSA forcefully combats corruption and enhance political stability, they are likely to witness not only a direct improvement in its economic performance but an indirect impact through poverty reduction. Secondly, the study examined the direct relationship between governance and public expenditure using balanced panel data for 1996-2019, employing the Pooled Mean Group (PMG) to tackle the problem of heterogeneity for the 34 selected SSA. The findings show that governance (corruption and political instability) in SSA countries increase public expenditure. Similarly, population growth and trade do impact public expenditure positively, whereas, debt service negatively affect public expenditure. Therefore, anti-corruption agencies in SSA countries should ensure enforcement of their laws and compliance with the code of ethics for public officers, while dealing with corrupt officials to scare others from stealing public funds, thereby generating sufficient revenue and usefully spending. Thirdly, the study investigated the relationship between governance and trade in the SSA region, using panel data of 38 countries for 1996-2019 employing the PMG estimation technique. The study finds that governance (corruption and political instability) decrease trade in the SSA countries. Hence, the government must ensure fighting corruption parallel with other actions to facilitate growth for exports, while making the bribery of officials a criminal offence. Also, political stability should be improved to attract higher FDI inflows to increase savings in the region, by and large, increasing trade.